The 12 biggest breakthroughs in gaming technology - Kallio, Jamie (Technology breakthroughs II., 2019)
Highlights twelve advances in gaming technology ranging from the first home game console released in 1972 and the evolution of video game controllers to modern mobile games and massively multiplayer games. Includes text-related questions, resource for further information, a QR code for further online resources, and color photographs.